Kyai Nurjalipah: Peran dan Pengaruhnya pada Ketatanegaraan Desa Perdikan Pakuncen Kab. Nganjuk (1651-1760 M) - Sazanah, Nurul Fatin; Nurcholis, Ahmad; Rohmah, Nurul Baiti (el Buhuth: Borneo Journal of Islamic Studies, 2023)
This research is a study of the role and influence of a village leader, namely Kyai Nurjalipah. The aim of this research is to explain the origins of Kyai Nurjalipah, his role and his influence in the field of state administration of the Perdikan Pakuncen Village in 1651-1760. The method used in this research is a historical research method by utilizing oral data sources through interviews and library sources. The results of this research showed that there is a close connection between Kyai Nurjalipah and the field of state administration of the Pakuncen Village. Kyai Nurjalipah can be said to be the 'owner' of the Pakuncen land because he was the person who opened that residential land. The development of Pakuncen Village is also inseparable from the role and influence of Kyai Nurjalipah, starting from his role as a spreader of Islam in the village, making Pakuncen as an important area of the Kadipaten Posono, his agreement with Mataram Palace that resulted in the changing status of the pakuncen into a perdikan land, until making policies to regulate villagers, which greatly affected the form of government, the condition of the population and culture of the village community at that time.